Inventory of Social Protection Programs in Myanmar - Infante-Villarroel, Mariana (World Bank, Washington, DC, 2015)
Myanmar’s spending on and coverage of social protection programs is low. Developing the building blocks of a social protection system needs to be a gradual process based on strengtheninginstitutional capacity and ensuring fiscal sustainability. Key social security reforms and the expansion of government-led social assistance programs can promote poverty reduction and help Myanmar address vulnerabilities in an effective and sustainable way. Development partners’ experience can be an important asset government can resort to when designing and implementing social assistance in Myanmar.